Assessing Biomechanical and Clinical Outcomes of an Elbow Orthosis Intervention in Youth Baseball: Preliminary Results - Gonzalo Mariscal; Carlos Barrios (MDPI AG, 2024)
Proper orthosis design may help youth baseball players develop safer pitching mechanics to prevent elbow injuries. This study evaluated the impact of a custom elbow orthosis on pitching biomechanics and adverse events. Ten 11-12-year-old players (mean age 11.5 years) from a regional league team were recruited. The inclusion criteria were at least two years of baseball experience. Six players were randomly assigned to the orthosis group, with four in the control group. Anthropometric data and baseline characteristics were recorded. A video analysis assessed elbow flexion angle during pitching at baseline and at 2 months. The frequency of orthosis wear was also tracked. Adverse events during twice-weekly practices were documented. Post-study surveys evaluated orthosis comfort, stability, and safety perceptions. In the orthosis group (n = 6), four participants showed improved elbow flexion angle, and two of the six participants showed almost no change. The overall median difference was 23.5°. In the control group (n = 4), three participants showed improvement, with a median improvement of 5.5°. Twelve adverse events, including pain, were reported by players not wearing orthoses, whereas no events occurred with orthosis use. Individual players in the control group or who did not wear the orthosis correctly experienced multiple episodes of pain from pitching over the study period. This preliminary study indicates a custom elbow orthosis can optimize pitching biomechanics and prevent adverse events in youth baseball players over the course of two months.